An experimental study on fear of public speaking using a virtual environment. - Slater, M; Pertaub, D; Barker, C; Clark, D (2006)
This paper examines a necessary condition for successful exploitation of a virtual environment (VE) in therapeutic intervention for fear of public speaking. The condition is that clients experience a degree of anxiety in the VE that is similar to what they would have been expected to experience in a similar real world setting. We refer to this as a "presence" response. The experimental study involved 20 people who were confident public speakers and 16 who were phobic, assessed on a standard psychological scale. Half of each group spoke within a VE depicting an empty seminar room, and the other half within the same room but populated by a neutrally behaving virtual audience of five people. Three responses were measured--a questionnaire-based measure of anxiety, a measure of self-focused attention on somatic responses, and actual heart rate. On all responses, the people with phobia showed a significant increase in signs of anxiety when speaking to the virtual audience compared to the empty room, whereas the confident people did not. The result was strong in spite of the relatively low representational and behavioral fidelity of the virtual characters.